Determinación de retos y oportunidades del campus CEASA frente a la economía circular como desarrollo sostenible en tiempos de pandemia Covid19, 2021. - Shiguango Chimbo, Lady Marlith (2021)
This research work aims to determine the challenges and opportunities of the CEASA campus in the face of the circular economy as sustainable development in times of the Covid19 pandemic. For which, a survey was conducted of research professors of the Environmental Engineering career of the CEASA campus of the CAREN Faculty in order to obtain answers about the current situation on campus and identify the most relevant challenges and opportunities, as well as doing the respective analysis. Establishing descriptive research as a methodology, for this purpose the inductive method was used accompanied by a bibliographic review with which important information on circular economy and sustainable development was collected. As a technique, a survey was made of 8 research teachers of the Environmental Engineering career in order to have an approach to the research problem. The research was complemented with the Tows method where the strengths, opportunities, weaknesses and threats were located to determine improvement strategies once the results of the survey were obtained. The most relevant challenges that could be identified are: 1. Ecodesign and manufacture of new products, incorporating a greater volume of recovered material resources and extending their durability. 2. Social recognition in search of economic resources to reduce pollution. 3. Change of attitude to improve processes and continuous improvement. The identified opportunities are: 1. To be a sustainable campus at the national level. 2. Generate innovation, quality management and transfer. 3. Create sources of income, environmental and economic models and research centers. On the other hand, in compliance with objective three, a proposal was established aimed at transferring to the circular economy model as CEASA's sustainable development strategy in response to the improvement strategies established in the Tows matrix. Regarding the scientific question, it was determined that more than 50% of the respondents answered that the Center Experimental Académic Salache is not yet prepared to be subject to circular economy procedures such as sustainable development, due to the existence of a series of weaknesses. and threats that make it difficult to carry out different activities that help the implementation of circular economy models and therefore the sustainability of the campus and due to the health crisis, it cannot continue 100% with the activities that contribute to the circular economy as sustainable development and this It has caused the opportunities that he had to diminish.